2014
DOI: 10.1007/s10897-014-9727-2
|View full text |Cite
|
Sign up to set email alerts
|

LQTS Parents’ Reflections About Genetic Risk Knowledge and their Need to Know or Not to Know their Children's Carrier Status

Abstract: Long QT syndrome (LQTS) is a contributor to unexplained deaths in infants (SIDS), children, teenagers and young adults. A gene test result may allow for individual tailored treatment, but also pose a burden of knowing one's carrier status, with no treatment recommendation. Genetic risk knowledge in the case of LQTS can promote adjustment and coping, but also fear anxiety, ambivalence and moral dilemmas. This makes it challenging to respect both the right to know and the right not to know. The purpose of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 22 publications
3
20
0
Order By: Relevance
“…Although these results may in part be due to the fact that 86 % of respondents were female, these findings are consistent with those found by D'AgincourtCanning, who concluded that women are more likely to be responsible for communicating health-related information to other family members [6]. In agreement with recommendations made by multiple studies, children's diagnoses were most commonly explained to them gradually over a period of time [2,8,11]. Further investigation revealed that the initial explanation was more likely to occur over a shorter period of time as the age of diagnosis increased.…”
Section: Communication Surrounding the Cardiomyopathysupporting
confidence: 89%
See 1 more Smart Citation
“…Although these results may in part be due to the fact that 86 % of respondents were female, these findings are consistent with those found by D'AgincourtCanning, who concluded that women are more likely to be responsible for communicating health-related information to other family members [6]. In agreement with recommendations made by multiple studies, children's diagnoses were most commonly explained to them gradually over a period of time [2,8,11]. Further investigation revealed that the initial explanation was more likely to occur over a shorter period of time as the age of diagnosis increased.…”
Section: Communication Surrounding the Cardiomyopathysupporting
confidence: 89%
“…However, minimal research has been published on how parents communicate risk information about cardiac diseases associated with SADS [8]. The primary objectives of this study included investigating how parents communicate with children about the children's diagnoses of cardiac diseases associated with SADS, exploring how the risk of sudden cardiac arrest is discussed, and determining which aspects of these conversations parents find most difficult to communicate to their child.…”
Section: Introductionmentioning
confidence: 99%
“…The clinician charged with disclosing the diagnosis should be familiar with all aspects of TS. He or she should set aside sufficient time to inform the parents and/or the patient about the various aspects of the diagnosis and treatment options (24). Experienced pediatric endocrinologists specialized in growth disorders should be involved in order to inform about the option of growth hormone (GH) therapy.…”
Section: Diagnostic Disclosurementioning
confidence: 99%
“…Others welcome genetic testing because a positive finding may enable them to take specific preventative measures for themselves and/or family members based on the precise genetic variant identified. Nevertheless, even those who elect to have genetic testing struggle with the implication of a positive result, worrying that disclosing a positive test result could have a negative impact on a family member [5]. …”
Section: Psychological Stress Associated With Cardiogeneticsmentioning
confidence: 99%